DINAMIKA KEBIJAKAN AUSTRALIA TERHADAP CHINA PASCA AUKUS: ANTARA KEAMANAN NASIONAL DAN KETERGANTUNGAN EKONOMI - Setiawan, Roy; Agustiani, Lutfia; Supriyadi, M; Pratiwi, Valenda (JURNAL ILMU SOSIAL DAN ILMU POLITIK, 2025)
This article discusses Australia's political dynamics in dealing with China since the formation of the AUKUS Security Alliance in 2021. Meanwhile, Australia is expanding its security cooperation with the United States and the United Kingdom to counter China's possible military expansion in the Indo-Pacific region. By participating in AUKUS, Australia can gain access to advanced defense technologies and strengthen its strategic position in the competition among major powers. Conversely, Australia maintains strong economic ties with China, one of its major trading partners in terms of strategic minerals. This study uses national interest concerns and complex interdependence to analyze the strategic dilemma Australia has to face, and points out the need to maintain national security without jeopardizing economic relations. The findings show that Australia has adopted a pragmatic strategy to enhance security guarantees and maintain stable diplomatic and economic relations with China. This approach supports Australia's efforts to maintain its strategic autonomy in an increasingly complex Indo-Pacific geopolitical environment.